Failure analysis of a leaked oil pipeline. (October 2015) - Yang, En-Na; Fu, Chang-Ming; Dong, Chen; Qu, Shen; Tian, Ji-Feng; Zhang, Zhe-Feng
Highlights: The leakage of an oil pipeline was analyzed via careful macro- and microscopic observations. The aggregation of pits, raised ridges and circular cracks were observed. Sufficient experimental evidences for liquid impingement erosion were provided. Abstract: An oil pipeline embedded in an underground trench had failed. Through the accident investigation we found that there was a perforation at the leak point of the pipeline. Macroscopic observation revealed that some pits collectively located at the exterior surface of the failed pipeline. In addition, raised ridges and circumferential cracks were observed inside the large pits with stereoscope and scanning electron microscope. After careful analysis it is concluded that the leakage of the pipeline was mainly caused by the liquid impingement erosion.